15p+11q+p-6q-4p=

Simple and best practice solution for 15p+11q+p-6q-4p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15p+11q+p-6q-4p= equation:


Simplifying
15p + 11q + p + -6q + -4p = 0

Reorder the terms:
15p + p + -4p + 11q + -6q = 0

Combine like terms: 15p + p = 16p
16p + -4p + 11q + -6q = 0

Combine like terms: 16p + -4p = 12p
12p + 11q + -6q = 0

Combine like terms: 11q + -6q = 5q
12p + 5q = 0

Solving
12p + 5q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5q' to each side of the equation.
12p + 5q + -5q = 0 + -5q

Combine like terms: 5q + -5q = 0
12p + 0 = 0 + -5q
12p = 0 + -5q
Remove the zero:
12p = -5q

Divide each side by '12'.
p = -0.4166666667q

Simplifying
p = -0.4166666667q

See similar equations:

| 3x^2-11+4=0 | | 8m+5n-6m+8n= | | (x+9)(x+12)=0 | | 7m+2n-2m+11n= | | x-80=40 | | 5.7m-3=2.7m+6 | | 1.45x+7(0.15x-2.8)=14.4 | | 5x-2=-18-3x | | 13-2x-5x+9= | | 2.5x-(40+1.75x)=550 | | 0.7=0.4+x-0.35 | | 20x+12=0 | | 16+2(x+4)(x-4)-x=-x+16 | | 6(y-1)-2y=2(2y-3) | | 0.7=0.4+P(B)-0.35 | | .25x-.75y=-1 | | 7.4x-4-5.2x=2.6 | | 4(5x+4)=3x+36+7x | | x^2+3y=-1 | | 8(m+6)+4=36+5m | | -3.6x+1.3=-16.7 | | 21x+6=23x-2 | | G(x)=x^2-x-5 | | -2.1-1.5=x+1.3 | | 3=t+5-3t | | 4x-5=6x+3 | | 2(x+5)=2x-5 | | 6=v+0.84 | | -50-0.25=-75 | | 110x=90(2-x) | | 1.29+3.9-9.99+6.1= | | X-3(x-5)=2x-11 |

Equations solver categories